Cancer risk among users of oral contraceptives: cohort data from the Royal College of General Practitioner's oral contraception study. Issue 7621 (11th September 2007) - Hannaford, Philip C; Selvaraj, Sivasubramaniam; Elliott, Alison M; Angus, Valerie; Iversen, Lisa; Lee, Amanda J
Abstract : Objective To examine the absolute risks or benefits on cancer associated with oral contraception, using incident data. Design Inception cohort study. Setting Royal College of General Practitioners' oral contraception study. Participants Directly standardised data from the Royal College of General Practitioners' oral contraception study. Main outcome measures Adjusted relative risks between never and ever users of oral contraceptives for different types of cancer, main gynaecological cancers combined, and any cancer. Standardisation variables were age, smoking, parity, social class, and (for the general practitioner observation dataset) hormone replacement therapy. Subgroup analyses examined whether the relative risks changed with user characteristics, duration of oral contraception usage, and time since last use of oral contraception. Results The main dataset contained about 339 000 woman years of observation for never users and 744 000 woman years for ever users. Compared with never users ever users had statistically significant lower rates of cancers of the large bowel or rectum, uterine body, and ovaries, tumours of unknown site, and other malignancies; main gynaecological cancers combined; and any cancer. The relative risk for any cancer in the smaller general practitioner observation dataset was not significantly reduced. Statistically significant trends of increasing risk of cervical and central nervous system or pituitary cancer, and decreasing risk of uterine body and ovarian malignancies, were seen with increasing duration of oral contraceptive use. Reduced relative risk estimates were observed for ovarian and uterine body cancer many years after stopping oral contraception, although some were not statistically significant. The estimated absolute rate reduction of any cancer among ever users was 45 or 10 per 100 000 woman years, depending on whether the main or general practitioner observation dataset was used. Conclusion In this UK cohort, oral contraception was not associated with an overall increased risk of cancer; indeed it may even produce a net public health gain. The balance of cancer risks and benefits, however, may vary internationally, depending on patterns of oral contraception usage and the incidence of different cancers.